(untitled) (Scottish Historical and Archaeological Internet Reports, 2004)
Specialist report on two skeletons, an adolescent and an older male. Both were in poor health and there is evidence to suggest that they were excarnated. In other words, they had lain exposed above ground prior to formal burial.